2011
DOI: 10.1080/15287394.2011.550563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Produced Water on Reproductive Parameters in Prespawning Atlantic Cod (Gadus morhua)

Abstract: Produced water (PW) discharged from offshore oil industry activities contains substances that are known to contribute to a range of mechanisms of toxicity. In the present study selected reproductive biomarkers were studied in prespawning Atlantic cod (Gadus morhua) exposed to PW. The fish were exposed for 12 wk within a continuous flow-through system at realistic environmental near-field concentrations. Concentrations of polyaromatic hydrocarbon (PAH) and alkylphenol (AP) compounds were analyzed by gas chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Our data bolster the growing body of evidence that hydrocarbon exposure can alter egg production in female fish (Brown‐Peterson et al ; Perrichon et al ; Raimondo et al ) and decrease reproductive fitness in male fish by reducing fertilization rate (Booc et al ). Hydrocarbons have also been shown to reduce sperm quantity (Sundt and Bjorkblom ) and quality (Nagler and Cyr ) and delay spermiation (Khan ), though those endpoints were not assessed in the present study. Correlation analyses revealed that tissue concentrations of parent and alkyl PAHs were negatively correlated with both egg production and fertilization rate, providing additional supportive evidence that the changes observed in egg production and fertilization rate in the present study are a result of hydrocarbon exposure and not natural variation between tanks.…”
Section: Discussionmentioning
confidence: 89%
“…Our data bolster the growing body of evidence that hydrocarbon exposure can alter egg production in female fish (Brown‐Peterson et al ; Perrichon et al ; Raimondo et al ) and decrease reproductive fitness in male fish by reducing fertilization rate (Booc et al ). Hydrocarbons have also been shown to reduce sperm quantity (Sundt and Bjorkblom ) and quality (Nagler and Cyr ) and delay spermiation (Khan ), though those endpoints were not assessed in the present study. Correlation analyses revealed that tissue concentrations of parent and alkyl PAHs were negatively correlated with both egg production and fertilization rate, providing additional supportive evidence that the changes observed in egg production and fertilization rate in the present study are a result of hydrocarbon exposure and not natural variation between tanks.…”
Section: Discussionmentioning
confidence: 89%
“…If some studies have reported no gonadal disruptions [ 17 , 43 ], some experimental exposure to PAHs as well as analysis of fish collected in the field in PAH-contaminated areas revealed disruption of gonadal structure or reproduction-related biomarkers, which could help to understand the presently observed reproductive defects. For example, some studies showed that fish exposure to PAHs results in gonadal structure disruption indicative of maturation defects in females [ 39 , 40 , 44 ] and in males [ 44 , 45 ]. Our results are in agreement with these articles, revealing a decrease in ovary maturation as shown by a decrease in mature follicles (F4) proportion in female exposed to 3X concentration for all fractions and post-vitellogenic follicles (F3) for HO-3X females.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of PY females, we have also identified degeneration areas in ovaries, the relative surface of which increased with PY concentration. In the case of males, the observed defects (hypoplasia in a small proportion of LO-3X and HO-1X and in a high proportion (42%) of HO-3X males) have already been mentioned in cod after exposure to produced water [ 44 ]. Further, one ovo-testis was also found in one individual morphologically identified as a male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less specifically, English sole (Parophrys tetulus) captured in areas contaminated with PAHs also had lower steroid concentrations (Johnson et al, 1988). Exposure of Atlantic cod (Gadus morhua) to produced water from the oil industry (containing PAH) also showed reduced E2 concentrations (Sundt and Bjorkblom, 2011). Contrary to these results, juvenile areolated grouper (Epinephelus areolatus) exposed to B[a]P in their diet showed large fluctuations in E2 and T concentrations and a significant elevation of T (Wu et al, 2003).…”
Section: Enzymementioning
confidence: 78%